VD_FINDINFO HC / 2011 / 94 vom 7. Dezember 2010 - VD Tribunal cantonal (2010)
CONCOURS D'INFRACTIONS, VIOLATION DES RÈGLES DE LA CIRCULATION, ORDONNANCE DE RENVOI | 49 al. 1 CP, 411 let. g CPP, 90 ch. 2 LCR